THE IMPACT OF CHEMICAL IMPURITIES IN DRINKING WATER ON THE HEALTH RISK OF NOVOKUZNETSK RESIDENTS - Кислицына, Вера Викторовна; Суржиков, Дмитрий Вячеславович; Голиков, Роман Анатольевич; Ликонцева, Юлия Сергеевна (Medicine in Kuzbass, 2025)
The aim of the study is to determine, based on risk assessment, the impact of chemical contamination of drinking water on the health of Novokuznetsk residents.Materials and methods. The study was conducted in a large industrial center of the Kemerovo region – the city of Novokuznetsk. Average annual concentrations of 18 chemical impurities in drinking water for 2021-2023 were analyzed. Non-carcinogenic and individual carcinogenic risks to public health were calculated.Results. The average concentrations of the studied chemical impurities in the city’s tap water do not exceed hygienic standards. Non-carcinogenic risk is at a minimum level, all hazard coefficients for chronic peroral intake of substances do not exceed 0.1. The maximum contribution (39.1%) to the formation of non-carcinogenic risk is made by chloroform (HQ was 0.086). The main crucial organs and systems of consumers are blood (HI is 0.16), central nervous system (HI = 0.10), kidneys (HI = 0.097). The priority impurities affecting the blood are manganese, nitrates and chloroform; manganese and chloroform influence on the central nervous system, and chloroform and cadmium – on the kidneys. The total individual carcinogenic risk (CR) was 1.44 × 10-5, which exceeds the acceptable level (1 × 10-5). The main contribution to the formation of this type of risk is made by bromodichloromethane (44.2%), chloroform (36.3%), dibromochloromethane (10.0%), cadmium (7.5%).Conclusion. The content of chlorine compounds in tap water determines the formation of a carcinogenic risk to the health of consumers even at the concentrations of chemical impurities below established hygienic standards.
Keywords: health risks; drinking water; chemical impurities; centralized water supply system; industrial city